Machine learning with AWS : explore the power of cloud services for your machine learning and artificial intelligence projects - Jackovich, Jeffrey (Packt Publishing Ltd, 2018)
In this book, you will learn about the various artificial intelligence and machine learning services available on AWS. Through practical hands-on exercises, you'll learn how to use these services to generate impressive results. By the end of this book, you will have a basic understanding of how to use a wide range of AWS services in your own ...